Comparing absolute and standardized drought indices for modelling tree mortality of spruce, beech, pine, and oak based on the Crown Condition Survey in Germany - Laura-Marie Schotte; Angelika Olesch; Sebastian Fuchs; Luca Smekal; Bernd Ahrends (Forest Ecology and Management, 2026)

Evaluating landscape-level pesticide exposure from spray drift: A modeling study in an agriculture-dominated watershed using SWAT+ and DAD-Drift - Mike Devin Fuchs; Sebastian Gebler; Andreas Lorke (Environmental Pollution, 2026)

Adhesion-adapted polymer coating systems as filmic model systems for homogeneous geometry-independent surface coating for cleaning analyses - Susanne Höhne; Petra Uhlmann; Vincent Eisenrauch; Sebastian Jacob; Carolin Böhm; Hannes Kettner; Eva Bittrich; Enrico Fuchs; Jens-Peter Majschak; Marc Mauermann (Food and Bioproducts Processing, 2026)

A single specific and actionable swap recommendation can lead to substantial reductions in households’ dietary carbon footprints - Kevin O'Sullivan; Verena Tiefenbeck; Matthias Stucki; Sebastian Bradford; Klaus Ludwig Fuchs; Silvan Wanner; Elgar Fleisch (Journal of Cleaner Production, 2025)

The Local Turn in a Global Sea: Identifying Sustainability Trade‐Offs in Regionalized Marine Aquaculture Systems - Gesche Krause; Ramón Filgueira; Nesar Ahmed; Karen A. Alexander; Furqan Asif; Lucia Fanning; Sebastian C. A. Ferse; Nike Fuchs; Jon Grant; Jordi Guillen; Christina Hörterer; Teresa R. Johnson; et al. (Reviews in Aquaculture, 2025)
Marine aquaculture, like the broader seafood industry, relies heavily on international trade and global supply chains for both production and sales. Recent global disruptions, including the COVID‐19 pandemic, the Russian invasion of Ukraine, the conflicts in the Middle East, and trade tensions, have exposed the social and economic vulnerabilities inherent in a globalized production system. In response, these events have sparked growing interest in transitioning to localized and regional supply chain models. Calls to “buy national” and support domestic economies highlight this trend toward regionalization. This study explores the sustainability implications of regionalizing marine aquaculture by examining the four key segments of the supply chain. These are (1) upstream inputs and resources (2) aquaculture production (3) downstream added value‐processing and (4) distribution–transportation. Potential benefits of regional production models include increased resilience to disruptions, lower transportation‐related carbon emissions, and support for local economies. However, such models may also introduce trade‐offs, including reduced production efficiency, supply and sales limitations, and implications for social, cultural, and governance structures. Our analysis reveals that the sustainability outcomes of regionalization are complex and context‐dependent. It is influenced by the specific characteristics of existing supply chains and the regional contexts in which they operate. While regionalization may offer advantages in certain contexts, it does not guarantee improved sustainability. Thus, it is crucial to critically assess the assumption that regionalization inherently leads to improved sustainability outcomes. Proactive evaluation of these dynamics is essential to develop strategies that maximize benefits while addressing potential trade‐offs.

Landscape-level assessment of spray drift – A virtual experiment using the Droplet and Atmospheric Dispersion drift (DAD-drift) model - Mike Devin Fuchs; Sebastian Gebler; Andreas Lorke (Environmental Modelling & Software, 2025)

Clustering of compound events based on multivariate comonotonicity - Fabrizio Durante; Sebastian Fuchs; Roberta Pappadà (Spatial Statistics, 2025)

The droplet and atmospheric dispersion drift (DAD-drift) model – A modular approach for estimating spray drift at the landscape scale - Mike Devin Fuchs; Sebastian Gebler; Andreas Lorke (Environmental Research, 2025)

Effects of aluminosilicate-based additives on potassium release and ash melting during biomass combustion - Hendrik Mörtenkötter; Manas Kulkarni; Lennart Fuchs; Florian Kerscher; Sebastian Fendt; Hartmut Spliethoff (Fuel, 2024)

The In-Ga-Sb association of the post-Variscan Zn-Pb-Ag vein deposit at Lautenthal, Upper Harz Mountains, Germany: sphalerite mineral chemistry - Torsten Graupner; Sören Henning; Simon Goldmann; Sebastian Fuchs; Klaus Stedingk; Wilfried Liessmann; Sven Birkenfeld (Mineralium Deposita, 2024)
The Lautenthal sphalerite-galena vein deposit is part of the world-class Upper Harz Pb-Zn-Ag district in the Harz uplift block of the Paleozoic Variscan fold belt in Germany. Its sphalerite-dominated mineral association was studied using bulk-ore chemistry, electron probe microanalysis, and laser ablation-ICP-mass spectrometry. Gallium and locally In are the main high-tech-relevant trace elements hosted by sphalerite, with up to 150 ppm Ga and up to 380 ppm In in hand-picked sphalerite samples (mean In/Zn, 0.70 × 10 −3 ). Ore concentrates (≤ 50 kg) contain up to 65 ppm Ga and up to 109 ppm In (mean In/Zn, 0.36 × 10 −3 ). Accessory Fe-Co-rich gersdorffite-1 occurs in the earlier quartz-sulfide ore stage and Sb-rich gersdorffite-2 in the later carbonate-sulfide stage. Enrichment patterns of In are either defined by overprinting textures in the Fe-richer sphalerite-1 of the earlier stage, or relate to primary growth zoning in Fe-poor sphalerite-2 of the later stage. Using the sphalerite geothermometer GGIMFis, formation temperatures (median) of sphalerite-1 were estimated at ~ 230 °C for the Lautenthal orebody and at ~ 175 °C for the Bromberg orebody, which may indicate lateral T-zonation for the earlier ore stage. Sphalerite-2 data indicate formation temperatures of ~ 185 °C (median). Copper-bearing brines of the carbonate-sulfide stage with assumed temperatures of ~ 250 °C initiated replacement of In-poor sphalerite-1 by chalcopyrite and remobilization of Zn and trace elements. Indium-rich sphalerite-2 occurs associated with calcite and fine-grained galena. A direct spatial or temporal link of ore formation to a magmatic-hydrothermal system is unlikely, which contrasts to In-rich epithermal and tin-polymetallic vein deposits worldwide.

The fungal predominance in stem collar necroses of Fraxinus excelsior: a study on Hymenoscyphus fraxineus multilocus genotypes - Sandra Peters; Nina Gruschwitz; Steffen Bien; Sebastian Fuchs; Ben Bubner; Viktoria Blunk; Gitta Jutta Langer; Ewald Johannes Langer (Journal of Plant Diseases and Protection, 2024)
Over the past decades, European ash trees in Germany have been affected by ash dieback, reducing their vigour and mechanical resistance. Those trees that also have stem collar necroses and the resulting stem rot are particularly affected. In this study, multilocus genotypes (MLGs) of Hymenoscyphus fraxineus and their interactions with other fungi from stem collar necroses were analysed. Ten ash trees from three different adjacent forest stands in central Germany were sampled. A total number of 716 isolates were obtained from stem collar necroses from these ten trees. Microsatellite analysis was successfully performed on 274 isolates identified as H. fraxineus and 26 MLGs were revealed. The number of MLGs varied from one to seven per tree and did not correspond to the number or severity of necroses. A striking result was that five of the MLGs occurred in two trees. All other MLGs occurred independently in only one tree, as expected. Our data show that when multiple MLGs were observed in a tree, one of the MLGs outnumbered the others, indicating that H. fraxineus is a primary coloniser of stem collar necroses. A total of 61 morphotypes, including H. fraxineus , were identified and discussed, comprising endophytic, saprotrophic and pathogenic fungi. Between five and 19 different fungi were found per stem collar necrosis. The majority of all isolated morphotypes were Ascomycota (82%), with the most common orders being Xylariales and Hypocreales . The most frequently isolated morphotypes, apart from H. fraxineus , were Armillaria sp. and Diplodia fraxini . Together they account for more than three quarters of all assigned isolations. Apart from H. fraxineus , only Diplodia fraxini was isolated from all ten trees.

Ash dieback assessments on intensive monitoring plots in Germany: influence of stand, site and time on disease progression - Sebastian Fuchs; Henriette Häuser; Sandra Peters; Luisa Knauf; Felix Rentschler; Georgia Kahlenberg; Ralf Kätzel; Jan Evers; Uwe Paar; Gitta Jutta Langer (Journal of Plant Diseases and Protection, 2024)
Since 2002, ash dieback caused by the invasive fungus Hymenoscyphus fraxineus has been observed in Germany. The pathogen and its associated symptoms have fatal consequences for the vitality and survival of European ash ( Fraxinus excelsior L.), an economically and ecologically important tree species. This study analyses the ash monitoring results of eleven intensive monitoring plots of the FraxForFuture research network distributed across Germany and focuses on within-stand differences of symptoms in dependence of small-scale site and tree properties. A cohort of 1365 ash trees was surveyed six times over three years, testing and applying a summer and a winter version of a nationally standardised ash dieback assessment key. The main disease symptoms (crown dieback and basal lesions) were more pronounced in areas with higher ash density, in edaphically moist areas (hydromorphic soils), on younger/smaller ash trees, and generally increased over time. However, the trend over time differed between single plots. In case of considering only the surviving part of the ash populations, crown condition even improved in 6/11 plots, indicating a selection process. Large basal lesions at the beginning of the observation period were a very good predictor for deadfall probability, especially on trees with lower stem diameter. Generally, ash dieback related symptoms at stem and crown were highly correlated. Silvicultural management practice in the past that actively pushed ash towards the moister end of its water demand spectrum has to be questioned in the light of ash dieback. Cost-intensive ash re-cultivation in the future—possibly with less dieback-susceptible progenies—should avoid pure ash stands and hydromorphic soil conditions.

The ad-libitum taste test as measure of momentary alcohol use in the laboratory: an investigation of construct validity and confounding factors - Sebastian Trautmann; Anja Kräplin; Markus Muehlhan; Fée Ona Fuchs; Beate Loesch; Charlotte Wittgens (Psychopharmacology, 2024)
Rationale The ad-libitum taste test is a widely used covert measure of motivation to consume alcohol in the laboratory. However, studies on its construct validity and potential confounding factors are scarce. Objectives This study aimed to evaluate the construct validity of the ad-libitum taste test by examining the association of ad-libitum alcohol consumption with typical alcohol use and craving, and investigating potential moderation by trait anxiety, depressiveness, current mood, and drinking motives. Methods A sample of 264 young male individuals were offered two 0.33 l glasses of beer. Participants were instructed to rate the characteristics of each drink, while the percentage of beverages containing alcohol consumed was assessed. Associations of ad-libitum consumption with typical alcohol use and craving were assessed using non-parametric and piecewise regressions. Moreover, moderator analysis with trait anxiety, depressiveness, current mood, and drinking motives was carried out. Results Ad-libitum alcohol consumption was associated with typical alcohol use and alcohol craving. However, these associations decreased at high consumption levels. Associations between ad-libitum consumption, typical alcohol use, and craving were stable across several conditions, except that the association between ad-libitum consumption and craving increased with higher social, conformity, and coping drinking motives. Conclusions The ad-libitum taste test appears to be a valid measure of the motivation to drink alcohol in laboratory studies in young male adults, although this validity might be compromised at high levels of ad-libitum consumption. Consideration of these factors can contribute to further refining the ad-libitum taste test as a valuable tool for assessing motivation to consume alcohol in laboratory studies.

Conceptualizing sustainable participation in the context of German football supporters - Sebastian Björn Bauers; Sandy Adam; Michael Fuchs; Leon Piotrowski; Gregor Hovemann (German Journal of Exercise and Sport Research, 2024)
Institutionalized supporter participation is a traditional part of German professional football clubs. Due to commercialization, some challenging issues have arisen in recent years regarding supporter participation. To develop new approaches for improving participation, the study uses a social sustainability perspective, illustrating that social sustainability elements help to develop and structure the potential for improvement of participation in German professional football. By identifying and discussing links between social sustainability and institutionalized supporter participation, we contribute to the conceptualization of sustainable participation. Our research supports the creation of an inclusive and sustainable fan community where fans can actively participate in decisions and actions that affect their current and future fandom environment. Based on the social sustainability principles of health, influence, competence, impartiality, and meaning-making, we compile the following characteristics of sustainable participation: social well-being oriented participation, direct influence, regular voting rights, representative participation, appealable resolutions, information-based participation, barrier-free participation, democratic voting, established constitutions, and encouraged participation. This conceptualization provides approaches and foundations for future investigations regarding participation research in football and practical implications for member associations, association members, league organizers, and other stakeholders to establish and improve institutionalized participation.

Fungi associated with stem collar necroses of Fraxinus excelsior affected by ash dieback - Sandra Peters; Sebastian Fuchs; Steffen Bien; Johanna Bußkamp; Gitta Jutta Langer; Ewald Johannes Langer (Mycological Progress, 2023)
In recent decades the vitality and physical stability of European ash trees in Germany have been reduced by European ash dieback, especially when associated with stem collar necroses and rots. This study was carried out to investigate the composition of the fungal communities associated with stem collar necroses. Filamentous fungi were isolated from 58 ash trees out of nine forest stands in northern, eastern, and central Germany. Obtained isolates were identified to a genus or species level by means of morphological and molecular analyses. In total 162 morphotypes including endophytic, saprotrophic, and pathogenic fungi were isolated. For 33 species found no prior reports from Fraxinus excelsior were recognised, including Cryptostroma corticale and Diplodia sapinea . None of the identified species were found at all studied sites, though Diplodia fraxini was the most common fungus with regard to frequency within all isolates , occurring at seven sample sites. This species is followed by Hymenoscyphus fraxineus , Armillaria spp., Neonectria punicea , Diaporthe cf. eres , Fusarium cf. lateritium , and Paracucurbitaria sp. in order of frequency within all isolates. The aforementioned species are characterised and analysed in respect to their occurrence in stem collar necroses and at sample sites. The influence of site conditions on the fungal composition was described for five intensively sampled sites with a minimum of five studied trees (Schwansee, Rhüden, Berggießhübel, Satrup, and Schlangen). The sampling site of Schlangen was further subdivided into four subplots with different positions in the terrain. In the remaining four extensive sample sites, either one or two trees, respectively, were sampled and analysed (Oranienbaumer Heide, Woltershausen, Wolfenbüttel, and Neuhege). Over all sample sites, fungal communities of symptomatic stem tissue are similar concerning the most frequent fungi, but vary greatly according to singularly isolated fungi.

Influence of steam-induced wetting of food- and cosmetic-based contaminants on the efficiency of clean-in-place processes of containers - Siegfried Beckmann; Enrico Fuchs; Sebastian Jacob; Marc Mauermann (Food and Bioproducts Processing, 2023)

FraxForFuture—research on European ash dieback in Germany - Gitta Jutta Langer; Sebastian Fuchs; Johannes Osewold; Sandra Peters; Falk Schrewe; Maia Ridley; Ralf Kätzel; Ben Bubner; Jörg Grüner (Journal of Plant Diseases and Protection, 2022)
European ash dieback caused by the alien, invasive ascomycete species Hymenoscyphus fraxineus currently represents, along with its side effects, the greatest threat to common ash ( Fraxinus excelsior ) trees in Europe. The disease is widely distributed in Germany and present in all regions where common ash is growing. In order to study European ash dieback in Germany and to develop management strategies to conserve common ash as a forest tree species, the concerted, interdisciplinary research project FraxForFuture was initiated. FraxForFuture consist of an association of five sub-networks: FraxConnect, FraxMon, FraxGen, FraxPath, and FraxSilva. In total, 27 individual projects conduct research on the epidemiology of the disease, the pathogen and the preservation of ash, including various control, breeding, and silvicultural strategies. The main goals of the FraxForFuture network and the sub-networks as well as essential information about the network of common research plots are provided.

Ecosystem transpiration and evaporation: Insights from three water flux partitioning methods across FLUXNET sites - Jacob A. Nelson; Oscar Pérez‐Priego; Sha Zhou; Rafael Poyatos; Yao Zhang; Peter D. Blanken; Teresa E. Gimeno; Georg Wohlfahrt; Ankur R. Desai; Beniamino Gioli; Jean‐Marc Limousin; Damien Bonal; et al. (Global Change Biology, 2020)
We apply and compare three widely applicable methods for estimating ecosystem transpiration ( T ) from eddy covariance (EC) data across 251 FLUXNET sites globally. All three methods are based on the coupled water and carbon relationship, but they differ in assumptions and parameterizations. Intercomparison of the three daily T estimates shows high correlation among methods ( R between .89 and .94), but a spread in magnitudes of T /ET (evapotranspiration) from 45% to 77%. When compared at six sites with concurrent EC and sap flow measurements, all three EC‐based T estimates show higher correlation to sap flow‐based T than EC‐based ET. The partitioning methods show expected tendencies of T /ET increasing with dryness (vapor pressure deficit and days since rain) and with leaf area index (LAI). Analysis of 140 sites with high‐quality estimates for at least two continuous years shows that T /ET variability was 1.6 times higher across sites than across years. Spatial variability of T /ET was primarily driven by vegetation and soil characteristics (e.g., crop or grass designation, minimum annual LAI, soil coarse fragment volume) rather than climatic variables such as mean/standard deviation of temperature or precipitation. Overall, T and T /ET patterns are plausible and qualitatively consistent among the different water flux partitioning methods implying a significant advance made for estimating and understanding T globally, while the magnitudes remain uncertain. Our results represent the first extensive EC data‐based estimates of ecosystem T permitting a data‐driven perspective on the role of plants’ water use for global water and carbon cycling in a changing climate.

Divining gold in seafloor polymetallic massive sulfide systems - Sebastian Fuchs; Mark D. Hannington; Sven Petersen (Mineralium Deposita, 2019)

Erratum to: New mouse models for metabolic bone diseases generated by genome-wide ENU mutagenesis - Sibylle Sabrautzki; Isabel Rubio-Aliaga; Wolfgang Hans; Helmut Fuchs; Birgit Rathkolb; Julia Calzada-Wack; Christian M. Cohrs; Matthias Klaften; Hartwig Seedorf; Sebastian Eck; Ana Benet-Pagès; Jack Favor; et al. (Mammalian Genome, 2014)

Clone libraries and single cell genome amplification reveal extended diversity of uncultivated magnetotactic bacteria from marine and freshwater environments - Sebastian Kolinko; Gerhard Wanner; Emanuel Katzmann; Felizitas Kiemer; Bernhard M. Fuchs; Dirk Schüler (Environmental Microbiology, 2013)
Summary Magnetotactic bacteria ( MTB ), which orient along the earth's magnetic field using magnetosomes, are ubiquitous and abundant in marine and freshwater environments. Previous phylogenetic analysis of diverse MTB has been limited to few cultured species and the most abundant and conspicuous members of natural populations, which were assigned to various lineages of the P roteobacteria , the N itrospirae phylum as well as the candidate division OP 3. However, their known phylogenetic diversity still not matches the large morphological and ultrastructural variability of uncultured MTB found in environmental communities. Here, we used analysis of 16 S rRNA gene clone libraries in combination with microsorting and whole‐genome amplification to systematically address the entire diversity of uncultured MTB from two different habitats. This approach revealed extensive and novel diversity of MTB within the freshwater and marine sediment samples. In total, single‐cell analysis identified eight different phylotypes, which were only partly represented in the clone libraries, and which could be unambiguously assigned to their respective morphotypes. Identified MTB belonged to the A lphaproteobacteria (seven species) and the N itrospirae phylum (two species). End‐sequencing of a small insert library created from WGA ‐derived DNA of a novel conspicuous magnetotactic vibrio identified genes with highest similarity to two cultivated MTB as well as to other phylogenetic groups. In conclusion, the combination of metagenomic cloning and single cell sorting represents a powerful approach to recover maximum bacterial diversity including low‐abundant magnetotactic phylotypes from environmental samples and also provides access to genomic analysis of uncultivated MTB .

New mouse models for metabolic bone diseases generated by genome-wide ENU mutagenesis - Sibylle Sabrautzki; Isabel Rubio-Aliaga; Wolfgang Hans; Helmut Fuchs; Birgit Rathkolb; Julia Calzada-Wack; Christian M. Cohrs; Matthias Klaften; Hartwig Seedorf; Sebastian Eck; Ana Benet-Pagès; Jack Favor; et al. (Mammalian Genome, 2012)

Erratum to: A Nebulized Gelatin Nanoparticle-Based CpG Formulation is Effective in Immunotherapy of Allergic Horses - John Klier; Sebastian Fuchs; Anna May; Ulrike Schillinger; Christian Plank; Gerhard Winter; Conrad Coester; Heidrun Gehlen (Pharmaceutical Research, 2012)

A Nebulized Gelatin Nanoparticle-Based CpG Formulation is Effective in Immunotherapy of Allergic Horses - John Klier; Sebastian Fuchs; Anna May; Ulrike Schillinger; Christian Plank; Gerhard Winter; Heidrun Gehlen; Conrad Coester (Pharmaceutical Research, 2012)

Impulswellen infolge Lawineneinstoß in den Speicher Kühtai - Helge Fuchs; Michael Pfister; Robert Boes; Sebastian Perzlmaier; Robert Reindl (WASSERWIRTSCHAFT, 2011)